Evaluating the Modulation of the Acoustic Startle Reflex in Children and Adolescents via Vertical EOG and EEG: Sex, Age, and Behavioral Effects - Giannopoulos, Anastasios E.; Zioga, Ioanna; Papageorgiou, Panos; Pervanidou, Panagiota; Makris, Gerasimos; Chrousos, George P.; Stachtea, Xanthi; Capsalis, Christos; Papageorgiou, Charalabos (Frontiers in Neuroscience, 2022)
Acoustic Startle Reflex (ASR) constitutes a reliable, cross-species indicator of sensorimotor and inhibitory mechanisms, showing distinct signature in cognitive aging, sex and psychopathological characterization. ASR can be modulated by the Prepulse Inhibition (PPI) paradigm, which comprises the suppression of reactivity to a startling stimulus (pulse) following a weak prepulse (30-500 ms time difference), being widely linked to inhibitory capabilities of the sensorimotor system. If the prepulse-pulse tones are more clearly separated (500-2000 ms), ASR amplitude is enhanced, termed as Prepulse Facilitation (PPF), reflecting sustained or selective attention. Our study aimed to investigate early-life sensorimotor sex/age differences using Electroencephalographic (EEG) recordings to measure muscular and neural ASR in a healthy young population. Sixty-three children and adolescents aged 6.2-16.7 years old (31 females) took part in the experiment. Neural ASR was assessed by two different analyses, namely Event-related Potentials (ERPs) and First-derivative Potentials (FDPs). As expected, PPF showed enhanced responses compared to PPI, as indicated by eye-blink, ERP and FDP measures, confirming the gating effect hypothesis. Sex-related differences were reflected in FDPs, with females showing higher ASR than males, suggesting increased levels of post-startle excitability. Intra-group age effects were evaluated via multi-predictor regression models, noticing positive correlation between age versus eye-blink and ERP responses. Attention-related ERPs (N100 and P200) showed distinct patterns in PPI versus PPF, potentially indicative for alterative attentional allocation and block-out of sensory overload. Screening measures of participants’ neurodevelopmental (assessed by Wechsler Intelligence Scale for Children, WISC-III) and behavioral (assessed by Child Behavior Checklist, CBCL) markers were also associated with increased N100/P200 responses, presumably indexing synergy between perceptual consistency, personality profiling and inhibitory performance. Conclusively, modulation of ASR by PPI and PPF is associated with biological sex and internal/external personality traits in childhood and adolescence, potentially useful to guide symptomatology and prevention of psychopathology.